Strengthening Field Education: An Integrated Model for Signature Pedagogy in Social Work - Debra Olson-Morrison; Tami Radohl; Geri Dickey (InSight, 2019)
Disciplines that incorporate field education into their curriculum face similar challenges around fidelity and tracking of the integration of course work, field learning, and attainment of educational competencies. In social work curriculum, field education is identified as its signature pedagogy (CSWE, 2015), underscoring the importance of in-vivo learning. In this paper, the author’s explore challenges associated with integration and assessment of competencies reflective of signature pedagogical principles through a social work lens. The authors propose a model for upholding field education as signature pedagogy through a combination of utilizing a faculty field liaison, housing field education within a course, and by instituting a comprehensive field education learning plan. While specific to social work, the model may generalize to other disciplines struggling to uphold quality in clinical and field education experiences.